The Effectiveness of Total Physical Response (TPR) in Improving English Instruction Comprehension for Sixth-Grade Students - Muchammad Sofyan Firman Syah; Syaefani Arif Romadhon (English Language Education Department, Universitas Majalengka, 2025)
This research aims to investigate the effectiveness of the Total Physical Response (TPR) method in increasing sixth-grade students' understanding of English instructions. The background of this study was the low ability of students at SD Muhammadiyah 1 Brebes to respond to teacher commands without translation. This study employed a quantitative approach with a pre-experimental design, specifically the One-Group Pretest-Posttest Design. The sample consisted of 16 sixth-grade students selected through purposive sampling in the academic year 2025. Data were collected using a listening comprehension test administered before and after the treatment. The data analysis revealed a significant improvement in student performance. The mean score of the pre-test was 52.18, while the mean score of the post-test increased to 80.31. The results indicate that the TPR method successfully helped students internalize English meaning through physical movement and reduced their learning anxiety. It is concluded that Total Physical Response is an effective strategy to enhance listening comprehension and student engagement among young learners.